DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR PERIODE 2017-2020 - Purnama, Benny; Dewi, Sofia Prima (Jurnal Paradigma Akuntansi, 2024)
This study aims to analyze the effect of capital structure, firm size, sales growth, liquidity, and profitability on fim value. This study uses secondary data obtained from financial statement and processed with Eviews 12. This study uses purposive sampling in determining the sample used. There are 57 manufacturing companies listed on IDX in 2016-2020 selected as sample. This study found that capital structure and profitability have a positive effect on firm value, firm size and sales growth have negative effect on firm value. Liquidity has no negative effect on firm value.